Economic Transformation and Human Development Index in Nigeria - Ovenseri-Ogbomo Friday Osaru; David Umoru (International Journal of Social Sciences & Educational Studies, 2017)
This research seeks to examine the impact of human development index (HDI) on economic transformation Nigeria. The paper adopted error correction mechanism to accentuate the dynamic paths of variables and aptitude of these variables to return to long-run equilibrium after a shock. From empirical results, it was found that HDI and school enrolment were most statistically significant in Nigerian growth equation. We thus recommend as a policy that emphasis human capital development in Nigeria most especially when the Nigerian nation is labor-intensive one.